Bacterial Etiology of Bloodstream Infections and Antimicrobial Resistance Patterns from a Tertiary Care Hospital in Malé, Maldives - Aishath Maharath; Mariyam Shabeena Ahmed (International Journal of Microbiology)
Background. Bloodstream infections pose a significant health problem worldwide and is a major cause of morbidity and mortality in many countries. It is important to have country-specific data for major pathogens causing bloodstream infections, in light of emerging resistance patterns of common bacterial isolates. Due to the scarcity of reports in this area, the aim of this study was to identify bacterial pathogens causing bloodstream infections among the study population. Methods. A retrospective analysis of blood culture samples received at the Department of Laboratory Medicine, Indira Gandhi Memorial Hospital, Malé, Maldives, was performed for reports between January 2016 and December 2017. Results. Out of the 471 culture-positive samples, 278 (59%) were males and 193 (41%) were females. Amongst the culture-positive samples, 338 (71.8%) Gram-positive organisms were isolated and 133 (28.2%) Gram-negative organisms were isolated. Coagulase-negative Staphylococcus (CoNS) was the most frequently isolated blood-borne bacterial pathogen in this study, accounting for 53.6% and 50.9% of the isolates in 2016 and 2017, respectively. Other frequently isolated pathogens included Staphylococcus aureus (15.9% and 10.3%), Klebsiella spp. (10.5% and 16.4%), and Escherichia coli (7.1% and 10.8%). Coagulase-negative Staphylococcus (CoNS) revealed high percentage of resistance among the tested antimicrobials, ampicillin, cephalexin, cefotaxime, and gentamicin. Over the two years, a significant difference between the percentage resistance among paediatric and adult patients was observed for coagulase-negative Staphylococcus (CoNS) isolate resistance to ampicillin p≤0.001, cephalexin p≤0.001, cefotaxime p≤0.001, gentamicin p=0.008, and cotrimoxazole (SXT) p≤0.001. When comparing the significant antimicrobial resistance trends, it can be seen that Enterobacteriaceae isolates also demonstrated high resistance to ampicillin and gentamicin as well as second- and third-generation cephalosporins. Conclusions. This study highlights the major bacterial pathogens involved in bloodstream infections in the healthcare setting of Malé, Maldives, and antibiotic resistance patterns. The results indicate that further characterization of bacteremia and its resistance patterns is needed to combat bloodstream infections.